Влияние возраста листьев сахарной свеклы на ПЦР-профили ферментных генов - Виниченко, Н.А.; Кирикович, С.С.; Левитес, Е.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. In the previous researches we showed that during a sprout growth process and a tissue differentiation there is a change of DNA structure of enzyme loci. These changes, however, do not concern primary structure of coding genes part. We were interested by a question, whether there is a change of DNA in adult plants. For this purpose we decided to use PCR-profiles of leaves of different age from one plant. Methods. For researches were taken two sugar beet agamospermous progenies. For receiving PCR-profiles we used the modified method of the ISSR analysis. The main peculiarity of this modification is those: together with a microsatellite primer for PCR we used the primer which was specific to the enzyme locus. DNA was extracted from the youngest, average and senior leaves. Results. PCR-profiles for Adh1, Me1, Gpi1, Got1 loci were received. A wide variety of PCR-profiles of Adh1 locus was revealed even in homozygous plants at all studied stages of growth. PCR-profiles of a Me1 locus did not show a wide variety, but showed gradual transition of one PCR-profile to another one during leaf growth. It was revealed complication of PCR-profiles of Gpi1 and Got1 loci during leaf development and growth. Conclusions. Obtained results point out that there are changes of DNA structure of enzyme loci the adult plant of sugar beet during development and growth of a leaf. At present there are no data which point that these changes connected with changes of the nucleotide sequences of studied genes.

Key words: PCR-profiles, sugar beet, enzyme loci, ISSR analysis.